Associations between diet, the gut microbiome and short chain fatty acids in youth with islet autoimmunity and type 1 diabetes. Issue 3 (1st February 2021) - Harbison, Jessica E.; Thomson, Rebecca L.; Wentworth, John M.; Louise, Jennie; Roth‐Schulze, Alexandra; Battersby, Rachel J.; Ngui, Katrina M.; Penno, Megan A. S.; Colman, Peter G.; Craig, Maria E.; Barry, Simon C.; Tran, Cuong D.; et al.
Abstract: Aim: We aimed to characterize associations between diet and the gut microbiome and short chain fatty acid (SCFA) products in youth with islet autoimmunity or type 1 diabetes (IA/T1D) in comparison with controls. Research design and methods: Eighty participants (25 diagnosed with T1D, 17 with confirmed IA, 38 sibling or unrelated controls) from the Australian T1D Gut Study cohort were studied (median [IQR] age 11.7 [8.9, 14.0] years, 43% female). A Food Frequency Questionnaire characterized daily macronutrient intake over the preceding 6 months. Plasma and fecal SCFA were measured by gas chromatography; gut microbiome composition and diversity by 16S rRNA gene sequencing. Results: A 10 g increase in daily carbohydrate intake associated with higher plasma acetate in IA/T1D (adjusted estimate +5.2 (95% CI 1.1, 9.2) μmol/L p = 0.01) and controls (adjusted estimate +4.1 [95% CI 1.7, 8.5] μmol/L p = 0.04). A 5 g increase in total fat intake associated with lower plasma acetate in IA/T1D and controls. A 5% increase in noncore (junk) food intake associated with reduced richness (adjusted estimate −4.09 [95%CI –7.83, −0.35] p = .03) and evenness (−1.25 [95% CI –2.00, −0.49] p < 0.01) of the gut microbiome in IA/T1D. Fiber intake associated with community structure of the microbiome in IA/T1D. Conclusions: Modest increments in carbohydrate and fat intake associated with plasma acetate in all youth. Increased junk food intake associated with reduced diversity of the gut microbiome in IA/T1D alone. These associations with the gut microbiome in IA/T1D support future efforts to promote SCFA by using dietary interventions.